Coronavirus disease (COVID-19) associated delayed-onset fulminant myocarditis in patient with a history of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Issue 12 (December 2021) - Ishikura, Hiroyasu; Maruyama, Junichi; Hoshino, Kota; Matsuoka, Yuta; Yano, Masaya; Arimura, Tadaaki; Katano, Harutaka; Kato, Seiya; Kitamura, Taisuke; Nakamura, Yoshihiko
Abstract: A healthy 35-year-old man was admitted to a rural hospital with coronavirus disease (COVID-19). During 14 days of hospitalization, he had no symptoms and was not given supplemental oxygen. About 3 weeks after discharge, he was re-admitted to the same hospital with new-onset continuous fever and general weakness. At the time of his second admission, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) RT-PCR was performed on a retro-nasal swab and the result was negative. Four days after admission, the patient was transferred to our intensive care unit (ICU) following deterioration of his respiratory and haemodynamic conditions, where he received mechanical ventilation, intra-aortic balloon pumping, and veno-arterial extracorporeal membrane oxygenation. A nasopharyngeal swab was obtained again at ICU admission, but RT-PCR was negative for SARS-CoV-2. All antibody titres measured against other viruses were low. Blood cultures were negative, and no bacteria were observed in sputum samples. However, SARS-CoV-2 RNA was detected by RT-PCR from sections obtained by myocardial biopsy. The patient's final diagnosis was delayed-onset SARS-CoV-2-induced fulminant myocarditis (FM). We strongly suggested that one of the proposed mechanisms of COVID-19-related myocardial injury will be the direct invasion of SARS-CoV-2 into cardiomyocytes even if delayed-onset. And this is the first case of delayed-onset FM in which diagnosis of active myocarditis was proven by pathological examination following endomyocardial biopsy and SARS-CoV-2 was detected in the myocardium by RT-PCR.